2017
DOI: 10.1007/s10389-017-0798-z
|View full text |Cite
|
Sign up to set email alerts
|

Gender influence on health and risk behavior in primary prevention: a systematic review

Abstract: Aim Prevention plays a crucial part in healthcare systems and is greatly influenced by the health and risk behavior of the population. The extent to which special tailoring to the addressed subjects would be helpful in improving the effectiveness of prevention measures is unknown. Therefore, the goal of this systematic review is to assess gender-specific differences in primary prevention actions. Subject and Methods A systematic review was conducted in 2015 by searching the PubMed (Medline) and Cochrane Librar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
36
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(47 citation statements)
references
References 33 publications
9
36
0
2
Order By: Relevance
“…Our findings also provide limited support for the TPB,25 since participant behavioral and control beliefs, subjective norms, and intentions changed after the intervention along with actual handwashing behaviors (although no post-intervention changes were seen in normative beliefs, attitudes, or PBC). These findings are consistent with those of other research that has shown that handwashing practices are influenced by beliefs27 and subjective norms 27,28,30. The corresponding increases in handwashing knowledge and practice in this study are also in line with previous findings that knowledge predicts healthcare providers’ hand hygiene behaviors 4,6,34…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our findings also provide limited support for the TPB,25 since participant behavioral and control beliefs, subjective norms, and intentions changed after the intervention along with actual handwashing behaviors (although no post-intervention changes were seen in normative beliefs, attitudes, or PBC). These findings are consistent with those of other research that has shown that handwashing practices are influenced by beliefs27 and subjective norms 27,28,30. The corresponding increases in handwashing knowledge and practice in this study are also in line with previous findings that knowledge predicts healthcare providers’ hand hygiene behaviors 4,6,34…”
Section: Discussionsupporting
confidence: 93%
“…There were large differences between self-reported and observed handwashing rates for the intervention group at all three assessments—a problem that has also been noted by other hand hygiene intervention researchers 27,43,4. Our participants had much higher self-reported (61%) than observed (18%) rates of handwashing at baseline and much smaller improvements in self-reported handwashing (7.5% increase) than observed practice (75% increase) at the immediate post-intervention assessment.…”
Section: Discussionsupporting
confidence: 60%
“…In a number of studies, it is reported that female respondents display better hand hygiene behaviors than males, independent of the studied group, as women are more likely than men to wash their hands, wash both hands, wash hands properly, and wash hands more often [ 28 , 29 , 30 , 31 ]. Similarly, in a systematic review analyzing the influence of gender on the health risk behaviors, it was indicated that handwashing behavior is included in the everyday hygienic behaviors mainly in the case of women [ 69 ]. Moreover, a significantly higher share of women than men practice proper hand hygiene behaviors when being observed by others, or in the presence of a sign reminding them to do it [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in polls nationwide, younger individuals (≤36 years of age) are less likely to report wearing masks and gloves and perceive fewer benefits of such protective practices [2,[9][10][11]14]. This is a peculiar behavioral pattern, as even before the pandemic, males and younger individuals in the U.S. were more likely to engage in riskier behaviors such as drug use and violence and less likely to practice general hygienic behaviors such as handwashing [15][16][17]. Unfortunately, according to preliminary reports, men have a higher risk of mortality from COVID-19, and deaths of younger individuals are not uncommon [17,18].…”
Section: Discussionmentioning
confidence: 99%